Musicals : Hollywood and beyond - Marshall, Bill, 1957-; Stilwell, Robynn Jeananne (Intellect, 2000)
"This original collection of essays seeks to initiate a new critical debate by approaching classic Hollywood films from perspectives such as 'musicology'. Broadening the scope of previous studies, this volume also examines the manner in which European cinema appropriated the musical to create new meanings. In addition, the book provides an innovative and up-to-date reading of the influence of the musical on youth culture today and its endorsement in modern dance movies, MTV and Music Video." "This is an accessible text for students on degree programmes in Film or Music both in the UK and US. It will also be a welcome resource for those researching and teaching in this area."--Jacket